Knowledge Regarding Basic Life Support Among Nurses of a Tertiary Level Hospital of Nepal - Bajracharya, Shanti; Nagarkoti, Liza (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Basic life support (BLS) is an emergency procedure that consists of recognizing an arrest and initiating proper cardio pulmonary resuscitation (CPR) techniques to maintain life until victims either recovers or is transported to medical facility where advanced life support are available. It is very important that all nurses know about basic life support to save lives of patients. Methods: A descriptive cross-sectional study was conducted in 50 nurses working in various intensive and high care units of our teaching hospital to assess their Knowledge on BLS. Non-probability purposive sampling technique was used for data collection for which self-administered semi-structured questionnaire was used. Results: Majority (46%) of the respondents were between 20 to 25 years of age. 52% of respondents were of Proficiency Certificate Level (PCL), 36 % of bachelor of nursing (BN) and 12% Bachelor of Science in Nursing (B.Sc Nursing). 36% respondents had working experience of 5-10 years and 6% of 10-15 years. All respondents had heard about BLS but 86% of them had never attended any BLS training. Most of the respondents (86 %) had seen CPR being done and more than half of the respondents (58%) had done CPR. 62% stated circulation, airway and breathing as the latest CPR sequence. 90% of the respondents said cardiac arrest is the indication of CPR. 66 % had inadequate knowledge, 32% had moderate knowledge while minority 2 % had adequate knowledge on Basic Life Support. Conclusion: Knowledge of Basic Life Support (BLS) among Nepalese nurses was inadequate in majority of cases. There was also no association between the knowledge and academic qualification or experience.